Prolonged Monsoonal Moisture Availability Preconditioned Glaciation of the Tibetan Plateau During the Mid‐Pleistocene Transition - Andreas Koutsodendris; Dirk Sachse; Erwin Appel; Christian Herb; Tobias Fischer; Xiaomin Fang; Jörg Pross (Geophysical Research Letters)
Abstract Paleohydrological data comprising pollen assemblages and leaf‐wax hydrogen isotopes (δDwax) from paleolake sediments in the Qaidam Basin (China) provide evidence for a link between increased moisture availability on the Tibetan Plateau and global cooling during the Mid‐Pleistocene Transition. Notably, they document the persistence of humid and cold conditions during Marine Isotope Stages 24–22 (936–866 ka) suggesting that boundary conditions favorable for extended glaciation on the Tibetan Plateau first developed at ~900 ka. Our δDwax results indicate a strong influence of proximal (monsoonal) moisture sources during that glacial, in agreement with the intensification of the interhemispheric moisture transport resulting from Antarctic ice volume increase at ~900 ka. The consistency of our results with other marine and terrestrial climate data sets suggests that extended glaciation on the Tibetan Plateau may have initiated ~500 ka earlier than previously assumed, implying that midlatitude ice sheets actively contributed to global cooling during the Mid‐Pleistocene Transition.